Pengendalian Sarang Nyamuk dan Kepadatan Jentik Aedes sp. di Kelurahan Kalumbuk Kecamatan Kuranji Kota Padang - Angelina -; Aidil Onasis; Awaluddin Awaluddin; Lindawati Lindawati; Asep Irfan (Jurnal Sehat Mandiri, 2024)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus transmitted through the bite of the Aedes sp mosquito. This disease is endemic in Padang City, where 11 sub-districts have been recorded as being infected with dengue fever, the 3 sub-districts with the highest number of dengue cases, one of which is Kuranji sub-district with the highest number of cases. The aim of this research was to determine the relationship between controlling mosquito nests and the density of Aedes sp larvae. in Kalumbuk Village, Kuranji District, Padang City. This research design is analytical observation with a cross sectional approach. The research was carried out in September - December 2023. The population of this study was 460 families. Using a proportional random sampling technique using the Slovin formula, a sample of 82 families was obtained, and the data analysis used was the chi-square test statistic. The results of the research show that the implementation of controlling mosquito nests in Kalumbuk Village, Kuranji District is classified as poor (46.3%), larval density does not meet the quality standards, namely 91.5% (<95%), there is a relationship between controlling mosquito nests and Aedes larvae density. sp. with a p-value of 0.003. Conclusion: there is a significant relationship between controlling mosquito nests and the density of Aedes sp larvae. in Kalumbuk Village, Kuranji District, Padang City. It is recommended that the Community Health Center conduct outreach and activate 1 house 1 jumantik and the community can control mosquito nests with the 3M Plus program periodically once a week so that it can break the chain of transmission of dengue fever.